2001
DOI: 10.1111/j.1747-1346.2001.tb00612.x
|View full text |Cite
|
Sign up to set email alerts
|

The South Carolina Confederate Flag: The Politics of Race and Citizenship

Abstract: The interest group and social movement mobilizations to remove the Confederate Jag, which had been /lying since 1962,from atop the South Carolina State Capitol dome provides an instance where large, issue-specific coalitions successfully expanded the scope of a conflict andframed an issue in a universalistic discourse of inclusive citiienship. The groups and movements seeking to keep the /lag on the dome of the capitol experienced cascading defections in part based on a narrow vision of histoty the political c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A statewide poll taken in December 1996 found modest support for Beasley’s proposal (52% to 43%). Interest groups coalesced on both sides of the issue: the Council of Conservative Citizens, the League of the South, and the Ku Klux Klan opposed the removal of the battle emblem (it is important to note that the CCC and the League of the South did not welcome the Klan’s involvement), while dozens of groups led by the National Association for the Advancement of Colored People and the South Carolina Chamber of Commerce agitated for its removal (Woliver et al, 2001). After a series of votes on proposals facially similar to Beasley’s (the legislature declined to directly vote on the Governor’s plan), the legislature rejected any plan to remove the battle emblem from the capitol dome.…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…A statewide poll taken in December 1996 found modest support for Beasley’s proposal (52% to 43%). Interest groups coalesced on both sides of the issue: the Council of Conservative Citizens, the League of the South, and the Ku Klux Klan opposed the removal of the battle emblem (it is important to note that the CCC and the League of the South did not welcome the Klan’s involvement), while dozens of groups led by the National Association for the Advancement of Colored People and the South Carolina Chamber of Commerce agitated for its removal (Woliver et al, 2001). After a series of votes on proposals facially similar to Beasley’s (the legislature declined to directly vote on the Governor’s plan), the legislature rejected any plan to remove the battle emblem from the capitol dome.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…8 White political leaders universally claimed that the flag’s placement was commemorative, and not motivated by racial malice. The state legislature debated removing the emblem in 1993, amidst concerns that the flag was a deterrent to international investment (Leib 1995; Woliver et al, 2001). These debates over the emblem led the legislature to propose a non-binding referendum on the flag in 1994, in which 76% of respondents voted to keep the battle emblem flying (oddly, the referendum was not voted on in an at-large election, but was tied to the Republican party primary (see Webster and Leib, 2001)).…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In addition, changing the frame of the flag debate from one focusing on race and the relative efficacy of the Confederacy to one about “inclusive citizenship” gave flag opponents the political capital necessary to advocate effectively for its removal from the statehouse dome. Their explanation for changing opinions is therefore focused on social movements and framing, rather than legislator preferences (Woliver, Ledford, and Dolan ).…”
Section: Explaining Support For the Confederate Flagmentioning
confidence: 99%
“…The political fight over the Confederate flag is often framed as ''heritage verses hate'' (Woliver, Ledford, and Dolan, 2001) and research explaining support for the Confederate flag has evaluated which of these two factors provides the best explanation. Studies among whites in Georgia (Clark, 1997;Reingold and Wike, 1998) and Mississippi (Orey, 2004) have generally concluded that conservative racial attitudes are more important than measures of southern heritage in explaining support for the flag.…”
Section: Explaining Support For the Confederate Flagmentioning
confidence: 99%